Catalogue of the type material of pseudoscorpions (Arachnida: Pseudoscorpiones) deposited in the Hungarian Natural History Museum, Budapest - Novák, János; Dányi, László (Zootaxa, 2018)
A catalogue of the pseudoscorpion types deposited in the Hungarian Natural History Museum (Budapest) is presented. The Collection of Soil Invertebrates at the Museum harbours type material of 60 described (49 valid) pseudoscorpion species or subspecies, belonging to 13 families and 33 genera. Most of these are types of species described by Ödön Tömösváry, Jenő Daday, Max Beier and Volker Mahnert, along with a handful described by Lodovico di Caporiacco, Mark Harvey and János Novák. Lists are also given of types of species that were, or might be expected to have been, deposited in HNHM but cannot now be located there. A lectotype is designated for Chelifer rutilans Tömösváry, 1883, which is considered a junior subjective synonym of Chelifer cancroides (Linnaeus, 1758) (syn. nov.).